(untitled) (Journal of Geography and Environmental Management, 2024)
The increased anthropogenic impact leads to an acceleration of loss and transportation of the surface fertile soil layer from the fields and the development of water and wind erosion processes. As a result, a phenomenon is recorded, conventionally described as follows: loss – transportation – accumulation of soils on slopes. A comprehensive review and evaluation of methods for calculating soil loss presented in scientific circles has been carried out. Kazakhstan, being an agro-industrial state, has certain risks associated with soil fertility. In this context, there is an urgent need for predictive scientific research based on determining the possible direction of development of potential soil loss. The article deals with the problem of the development of erosion processes in the virgin lands of Western Siberia and Northern Kazakhstan, developed in the 1950s. It is shown that plowing led to a sharp increase in water and wind erosion. Part of the arable land was abandoned due to the loss of fertility. Estimates of the rates of erosion processes during the development of stormwater runoff, obtained on the basis of the use of erosion models, are given. The necessity of using field methods for verification of calculations based on erosion models is stated. Field and remote methods for assessing water and wind erosion of soils are recommended.